Trends in Breast Cancer Prevention - Russo, Jose (Springer International Publishing : Imprint: Springer, 2016)
This volume, with contributions from the most recognized experts in preventive strategies in breast cancer, presents the accepted as well as the novel ideas that have been introduced for the prevention of breast cancer. There is no single preventive agent that can stop the incidence of breast cancer-the malignant disease most frequently diagnosed in women of all races and nationalities. Furthermore, its incidence around the globe is increasing in industrialized countries. The worldwide incidence of breast cancer has increased 30-40% since the 1970s, reaching an excess of 1,390,000 new cases and a mortality of more than 460,000 cases in 2015. Therefore, what is needed is the development of rational strategies for the prevention of this fatal disease.